A flexible solid-state supercapacitor based on a poly(aryl ether ketone)–poly(ethylene glycol) copolymer solid polymer electrolyte for high temperature applications. Issue 69 (11th July 2016) - Na, Ruiqi; Huo, Pengfei; Zhang, Xingrui; Zhang, Shuling; Du, Yinlong; Zhu, Kai; Lu, Yaning; Zhang, Menghan; Luan, Jiashuang; Wang, Guibin
Abstract : Here in we fabricated a high temperature flexible solid-state supercapacitor based on PAEK–PEG copolymers solid polymer electrolyte. As fabricated supercapacitor has excellent electrochemical performance at various operating temperature especially high temperature (120 °C). Abstract : In order to meet the requirement of high temperature applications, a high thermal stability solid polymer electrolyte is prepared with a poly(aryl ether ketone)–poly(ethylene glycol) copolymer ( i.e., PAEK–PEG) as a polymer host, and LiClO4 as an electrolyte salt. A novel flexible solid-state supercapacitor is then assembled by the resultant solid polymer electrolyte and activated carbon electrodes. The electrochemical properties of the supercapacitor are analyzed over a wide temperature range of 30–120 °C. The fabricated supercapacitor has excellent electrochemical performance especially at high temperature ( e.g. high specific capacitance of 103.17 F g −1 at 0.1 A g −1 and an energy density of 6.76 W h kg −1 with a power density of 9.55 W kg −1 at 120 °C). Simultaneously, this solid polymer electrolyte based supercapacitor possesses excellent flexible bending properties and outstanding cycle stability of negligible specific capacitance loss after 2000 cycles at various temperatures, demonstrating its feasibility as an energy device for high temperature applications.